MINIMIZAÇÃO DO CUSTO DO SERVIÇO DE POTÊNCIA REATIVA FORNECIDA PELOS GERADORES LEVANDO EM CONTA A RESERVA DE POTÊNCIA - Rodríguez, Yuri Percy Molina (2005)
In the operation of the power transmission system the problems of voltage/reactive power can occur at any time due the contingencies and/or alterations in the demand. Therefore, reactive services are necessary to perform the control in relatively small time periods to improve the operation state and avoid the degradation of the security and the reliability of the system.The ancillary service of reactive power can be contracted by the System Independent Operator of agents connected to the Electrical system, such as generators, capacitor/reator banks, static VAR compensators static, compensators synchronous, among others.The present work proposes a methodology for minimizing the price of the reactive power service considering the coupling between this ancillary service and the power reserve service and the power market as well. For evaluation of the performance, it is considering the method of payment for reserve allocated for service of reserve power, and tests to evaluate its impact in the cost of the reactive power by using the IEEE 14-buses and IEEE 30-buses test systems, are performed. Discussions and relevant conclusions are also reported.